Impact of Meghdoot Mobile App - A Weather-based Agro-advisory Service in Cold arid Ladakh - Yogesh Kumar; Kaneez Fatima, Mahendra Singh Raghuvanshi; Manjeet Singh Nain; Mehrajuddin Sofi (Indian Journal of Extension Education, 2022)
The study was conducted to evaluate the impact of the Meghdoot mobile application-a weather-based agro-advisory service in cold arid Ladakh during 2020-21. A random sample of 100 registered farmers was selected which included 25 farmers each from Stok and Stakna villages and 50 farmers from Bazgoo village of Leh district. The data indicated that farmers of Leh district were very belittling of newspapers followed by radio. Almost, 70 percent of registered farmers have followed information for agriculture practices through the Meghdoot application of agro-meteorology advisory services but non-registered farmers used to follow their traditional methods for agricultural practice due to a lack of knowledge of this application of agromet-advisory services. More than 50 percent of farmers agreed that this application provided weather information in the local language with a mean score of 0.55. Similarly, in the case of wheat, an average yield superiority of 16.71 percent was recorded in the case of registered farmers over non-registered farmers during 2020. The mobile application provided benefits to the registered farmers in comparison to nonregistered farmers of district Leh, Ladakh.